The mechanical properties of anisotropic polymers: progress report no. 7 - Darlington, M. W. (College of Aeronautics, 1969)
Part I General Developments The major part of the period under review was devoted to a study of the tensile creep properties of isotropic and uniaxially oriented Perspex sheets (standard grade) using the three heavy-duty creep rigs mentioned in the previous Progress Report (No. 6. September, 1968). Measurements of lateral contraction were made simultaneously with the tensile strain measurements during most of the creep tests. The creep rupture behaviour and optical anisotropy of the oriented sheets were also studied in an attempt to present a more complete picture of the behaviour of the material. Some of the early results of this work have already been published and copies sent to the Ministry. (Darlington and Saunders; 1969). Details of the complete work will be found in part II of this report. The two types of contraction extensometer described in Progress Report No. 5 were used during the Perspex studies and reasonable agreement was obtained between the results. The techniques required with the contraction devices were considerably improved during the period under review and the absolute validity of the contraction measurements is now more certain. Some comments on the general performance of the apparatus are given in section 2.8.4.